A Western dietary pattern is prospectively associated with cardio-metabolic traits and incidence of the metabolic syndrome. Issue 10 (15th May 2018) - Drake, Isabel; Sonestedt, Emily; Ericson, Ulrika; Wallström, Peter; Orho-Melander, Marju
Abstract: The aim of this study was to derive dietary patterns associated with cardio-metabolic traits and to examine whether these predict prospective changes in these traits and incidence of the metabolic syndrome (iMetS). Subjects from the Malmö Diet and Cancer Study cardiovascular cohort without cardio-metabolic disease and related drug treatments at baseline ( n 4071; aged 45–67 years, 40 % men) were included. We applied reduced rank regression on thirty-eight foods to derive patterns that explain variation in response variables measured at baseline (waist circumference, TAG, HDL- and LDL-cholesterol, systolic and diastolic blood pressure, fasting glucose and insulin). Patterns were examined in relation to change in cardio-metabolic traits and iMetS in subjects who were re-examined after 16·7 years ( n 2704). Two dietary patterns ('Western' and 'Drinker') were retained and explained 3·2 % of the variation in response variables. The 'Western' dietary pattern was inversely associated with HDL-cholesterol and positively with all other response variables (both at baseline and follow-up), but there was no association with LDL at follow-up. After adjustment for potential confounders, the 'Western' dietary pattern was associated with higher risk of iMetS (hazard ratio Q4 v. Q1: 1·47; 95 % CI 1·23, 1·77; P trend =1·5×10 −5 ). The 'Drinker' dietary pattern primarily explained variation in HDL and was not associated with iMetS. In conclusion, this study supports current food-based dietary guidelines suggesting that a 'Western' dietary pattern with high intakes of sugar-sweetened beverages and red and processed meats and low intakes of wine, cheese, vegetables and high-fibre foods is associated with detrimental effects on cardio-metabolic health.